Respuesta :
[tex]x^3=\boxed{x}\cdot x^2[/tex], and
[tex]\boxed{x}(x^2+2x+1)=x^3+2x^2+x[/tex]
Subtract this from [tex]x^3[/tex] to get a remainder of
[tex]x^3-(x^3+2x^2+x)=-2x^2-x[/tex]
[tex]-2x^2=\boxed{-2}\cdot x^2[/tex], and
[tex]\boxed{-2}(x^2+2x+1)=-2x^2-4x-2[/tex]
Subtract this from the previous remainder to get a new remainder of
[tex](-2x^2-x)-(-2x^2-4x-2)=3x+2[/tex]
[tex]3x[/tex] does not divide [tex]x^2[/tex], so we stop here.
What we've done is to write
[tex]\dfrac{x^3}{x^2+2x+1}=x-\dfrac{2x^2+x}{x^2+2x+1}[/tex]
then
[tex]\dfrac{x^3}{x^2+2x+1}=x-2+\dfrac{3x+2}{x^2+2x+1}[/tex]
and we stop here because the remainder term [tex](3x+2)[/tex] has a degree less than the degree of the denominator.
Alternatively, we can be a bit tricky and notice that
[tex]x^2+2x+1=(x+1)^2[/tex]
Now,
[tex](x+1)^3=x^3+3x^2+3x+1[/tex]
so that
[tex]\dfrac{x^3}{(x+1)^2}=\dfrac{(x+1)^3-(3x^2+3x+1)}{(x+1)^2}[/tex]
We can divide the first term by [tex](x+1)^2[/tex] easily to get
[tex]\dfrac{x^3}{(x+1)^2}=x+1-\dfrac{3x^2+3x+1}{(x+1)^2}[/tex]
Next,
[tex](x+1)^2=x^2+2x+1[/tex]
so that
[tex]\dfrac{x^3}{(x+1)^2}=x+1-\dfrac{3((x+1)^2-(2x+1))}{(x+1)^2}-\dfrac{3x+1}{(x+1)^2}[/tex]
[tex]\dfrac{x^3}{(x+1)^2}=x+1-3+\dfrac{6x+3}{(x+1)^2}-\dfrac{3x+1}{(x+1)^2}[/tex]
[tex]\dfrac{x^3}{(x+1)^2}=x-2+\dfrac{3x+2}{(x+1)^2}[/tex]
which is the same result as before.